FACTORS AFFECTING CONFIDENCE IN SPEAKING ENGLISH AMONG ELEMENTARY STUDENTS - Chrisfania Putri Wardasari, Enny Dewi Tribuono, Munawwir Hadiwijaya (CV. ADIBA AISHA AMIRA, 2024)
This research aimed to analyze the factors that contribute to a lack of self-confidence in English speaking among students. It also sought to present possible strategies to help students overcome this lack of self-confidence. The study used a qualitative research approach and was conducted at SDN Singosari. The participants were the English teacher and fifth-grade students at SDN Singosari during the 2023/2024 academic year. Data was collected through observations and interviews. The data analysis involved three steps: data reduction, data display, and drawing conclusions. The findings revealed that the key factors leading to a lack of self-confidence in speaking English were anxiety, shyness, fear of making mistakes, and insufficient vocabulary. To address these issues, the study proposed several potential strategies, including lowering students' anxiety in the classroom, improving their vocabulary, boosting their self-confidence, and facilitating group discussions.